Resorbable glass fibers coated with sizing agent and method for preparing same - Patents.com
By applying thermoplastic, absorbable and biocompatible compatible agents on glass fibers and combining them with glass fibers through silane coupling agents, the problem of insufficient bonding strength in the prior art is solved, and the biocompatibility and absorbability of the material is achieved, while simplifying the application process.
Patent Information
- Application Number
- JP2024547787
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-02-25
- Filing Date
- 2023-02-16
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2043-02-16
AI Technical Summary
In the prior art, glass fibers have insufficient bonding strength in composite materials, and the application method of sizing agents is complicated, making it difficult to ensure both strength and biocompatibility.
A glass fiber sizing agent containing thermoplastic, absorbable and biocompatible compatible compatible agents that are tightly bonded to the glass fiber by a silane coupling agent, significantly increasing the bond strength between the glass fiber and the polymer matrix.
The bonding strength of glass fibers in composite materials is significantly improved, ensuring the biocompatibility and absorbability of the material, while simplifying the application process of sizing agents.
Smart Images

Figure 2025507553000001 
Figure 2025507553000002 
Figure 2025507553000003
Abstract
Description
[Technical field]
[0001] The present invention relates to resorbable, biocompatible glass fibers coated with a sizing agent. The present invention further relates to a method for coating resorbable, biocompatible glass fibers and a kit of parts suitable for use therein. [Background technology]
[0002] Fiberglass is a high performance material used in many technical fields where excellent mechanical properties and relatively light weight are required, such as aerospace, automotive, marine, energy, sporting goods, household appliances and medical implants. They are often used in composites where the fibers, such as carbon or glass fibers, are embedded in a matrix of another dissimilar material, such as a polymeric material.
[0003] Composites containing glass fibers embedded in a polymer matrix are believed to be very useful for medical applications, especially for orthopedic implants for bone and cartilage repair. The composites can be made to be biocompatible and resorbable, meaning that when implanted, they are degraded and resorbed in the mammalian (e.g. human) body according to a controlled rate. This allows the production of implants that do not need to be removed from the body and therefore do not require reoperation.
[0004] The performance of these composites generally depends on many factors, such as the amount, type, length, thickness and alignment of the glass fibers, the content and properties of the matrix material, and the quality of the interfacial bond between the polymeric matrix material and the glass fibers. One method of improving the quality of the interfacial bond between the polymeric matrix material and the glass fibers is the application of a sizing agent.
[0005] Glass fiber sizing agents contain components with different functions. The main components are a film former (also called a compatibilizer) and a coupling agent.
[0006] The film former forms a thin film on the glass fibers and performs several functions. In particular, it improves the processability of the glass fibers and the performance of the final product. Among other things, it protects and lubricates the fibers, as well as holds them together during the manufacture of composites. In addition, perhaps counterintuitively, it also serves to spread the glass fibers during the wet impregnation step of composite manufacture. When the glass fibers are to be used in a composite in combination with a polymer matrix, the film former in the sizing agent is usually chemically similar to the polymer matrix of the composite. This improves the adhesion between the polymer matrix and the glass fibers. It also ensures good wetting of the sized glass fibers by the matrix polymer by lowering the surface energy. In this context, it should be noted that the surface of glass fibers is generally hydrophilic, while the polymer matrix often has hydrophobic characteristics.
[0007] In sizing agents compatible with thermoplastic polymer matrices, the film former is ideally covalently bonded, i.e., grafted, to the glass fiber surface via a coupling agent, e.g., a silane. Grafted film formers that are chemically similar to the hydrophobic matrix polymer can provide a strong interface between the matrix polymer and the glass fiber through adhesion and chain entanglement. This type of entanglement helps to efficiently transfer loads from the matrix polymer to the reinforcing fibers, thus providing high initial mechanical strength as well as strength retention in-vitro or in-vivo.
[0008] For sizing to be effective, it is of course necessary that the sizing agent be maintained on the glass during processing. According to JL Thomason, Glass fibre sizing: A review, Composites Part A 127 (2019) 105619, it is known that up to 80% of the sizing agent on glass fibres can be removed by extraction with acetone. This indicates that some of the film former, and possibly other components, may not be chemically bonded to the glass fibres, but instead may be physisorbed onto the surface. High levels of physisorbed sizing agent will limit the strength of the resulting composite and will adversely affect the strength retention of glass-reinforced composites, implants or devices in vivo. Summary of the Invention [Problem to be solved by the invention]
[0009] Thus, there is a need for stronger, biocompatible and resorbable composites, and for easier methods of making such products. There is also a need for better sizing materials and methods of applying such sizing materials to resorbable and biocompatible glass fibers. [Means for solving the problem]
[0010] The present invention relates to a resorbable, biocompatible glass fiber coated with a sizing agent, the sizing agent comprising a thermoplastic, resorbable, biocompatible compatibilizer covalently bonded to the glass fiber through a coupling agent having at least one silane moiety, the glass fiber having an apparent interfacial shear strength with a reference matrix polymer determined in a single fiber pullout test, the apparent interfacial shear strength being at least 10% higher than the apparent interfacial shear strength of a bare glass fiber with the same reference matrix polymer.
[0011] The present invention further provides a method for providing a sizing agent to resorbable, biocompatible glass fibers, comprising the steps of: a) glass fibers, a coupling agent having at least one epoxy moiety and at least one silanol group in a liquid medium; and a reaction product of the reaction of a compatibilizer with a volatile tertiary amine in a liquid medium, wherein the compatibilizer is a thermoplastic, resorbable and biocompatible polymer containing carboxylic acid end groups; coating the glass fibers with a sizing composition by contacting the glass fibers with a sizing composition; b) subjecting the coated glass fibers to a drying step; c) subjecting the dried coated glass fibers to a curing process at elevated temperature; d) subjecting the cured coated glass fibers to a step of evaporating the volatile tertiary amine. The present invention relates to the above method, comprising:
[0012] The sizing composition used in the method according to the present invention is preferably aqueous. It comprises the reaction product of a thermoplastic, resorbable and biocompatible polymer containing carboxylic acid end groups, i.e., a compatibilizer, with a volatile tertiary amine. Without wishing to be bound by theory, it is believed that this product comprises ionic clusters (e.g., in the form of alkyl ammonium carboxylate salts) that act as ionic emulsifiers, which preferentially occupy the interface between the dispersed compatibilizer and the surrounding water, resulting in a micro- or nano-dispersion. Thus, the volatile tertiary amine acts to promote the dispersion of the compatibilizer in water. In addition, in some embodiments, it also catalyzes the reaction of the compatibilizer with the silane coupling agent.
[0013] When the dispersion type compatibilizer and the silane coupling agent are applied onto the glass fiber in a liquid medium, a drying step is carried out. In the drying step, the liquid medium is removed. Furthermore, the silanol group of the coupling agent reacts with the glass fiber, and the resulting reaction water is also removed. Then, during the curing of the glass fiber, the alkyl ammonium carboxylate salt decomposes, regenerating the carboxylic acid functional group, which then reacts with the epoxy group of the coupling agent. Depending on the selection of the volatile tertiary amine, this reaction can be catalyzed by the tertiary amine that is also released in the decomposition of the alkyl ammonium carboxylate salt. The tertiary amine can be removed, for example, by evaporation through the application of a vacuum or an inert gas flow. In one embodiment, the process is controlled so that there is enough tertiary amine in the system to catalyze the reaction of the carboxylic acid group with the epoxy group from the silane coupling agent.
[0014] As mentioned above, the use of volatile tertiary amines in the compatibilizers facilitates dispersion in (aqueous) emulsions and suspensions without the need for additional, and possibly harmful, surfactants, since they are designed to function as temporary reactive surfactants. Moreover, the compatibilizers are designed to react with the epoxy groups of the silane coupling agents, resulting in high grafting efficiency onto glass, thereby promoting adhesion and physical interaction with the matrix polymer.
[0015] The invention further relates to a kit of parts for carrying out the method of the invention to obtain the coated glass fibers of the invention.The invention also relates to a composite comprising the sized glass fibers and to a medical device comprising said composite. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] The present invention relates to a resorbable and biocompatible glass fiber coated with a sizing comprising a thermoplastic, resorbable and biocompatible compatibilizer, the sizing being covalently bonded to the glass fiber through a coupling agent having at least one silane moiety. Sizing or size is understood herein to refer to a coating on the glass fiber comprising a coupling agent covalently bonded to the glass and covalently bonded to a compatibilizer. The glass fiber has an apparent interfacial shear strength with a reference matrix polymer determined in a single fiber pull-out test, the apparent interfacial shear strength being at least 10% higher than the apparent interfacial shear strength of a bare glass fiber with the same reference matrix polymer.
[0017] Coupling agents refer to compounds capable of providing a chemical bond between two dissimilar materials. Typically, these are molecules with functional groups capable of bonding with organic materials (e.g. polymers, e.g. polyesters) as well as molecules with functional groups capable of bonding with inorganic materials (e.g. glass, e.g. glass fiber). The coupling agents of the present invention contain at least one silane moiety. Here, silane is understood to refer to a (functional) group or molecule having four bonds with a central silicon atom. An example of a silane is silane tetrahydride, which is a silicon atom surrounded by four hydrogen atoms. The coupling agents will be described in more detail below.
[0018] A compatibilizer refers to a low molecular weight polymer that is miscible with the polymer matrix of the composite in which the glass fibers are to be incorporated. The reaction product of the volatile tertiary amine and the compatibilizer in the present invention is preferably designed to function as a temporary processing aid that promotes the dispersibility of the compatibilizer in aqueous emulsions and suspensions without the need for additional surfactants. It is preferred not to add additional surfactants because they may have deleterious effects, such as leaching from the product during manufacture or end use. The compatibilizer is designed to react with the coupling agent so that the compatibilizer has a high grafting efficiency on the glass, which promotes adhesion and physical interactions, such as chain entanglements, with the matrix polymer of the composite in which the sized glass fibers may be used. The compatibilizer is described in detail below.
[0019] Preferably, the dry weight of the sizing is at least 0.1% by weight of the coated glass fiber, more preferably at least 0.2% by weight of the coated glass fiber, in particular 0.3% by weight of the coated glass fiber, more preferably at least 0.4% by weight of the coated glass fiber, more preferably at least 0.5% by weight of the coated glass fiber, and even more preferably at least 0.6% by weight of the coated glass fiber. Preferably, the dry weight of the covalently bonded sizing agent is 5% by weight or less, in particular 3% by weight or less, more particularly 1.2% by weight or less of the coated glass fiber, more preferably 1.0% by weight or less of the coated glass fiber, even more preferably 0.8% by weight or less of the coated glass fiber, even more preferably 0.6% by weight or less of the coated glass fiber. Lower values, for example 0.3% by weight or less, are also possible. Here, the coated glass fiber is understood to refer to the glass fiber that contains the covalently bonded sizing agent, i.e., the coupling agent and the compatibilizer.
[0020] Throughout this text, references to glass fibers will be understood to refer to coated glass fibers, unless otherwise specified or apparent from the description.
[0021] Volatile tertiary amines are used in the method of the present invention and are removed through evaporation. It is preferred that the volatile tertiary amines are substantially removed, more preferably completely removed. Preferably, the amount of volatile tertiary amines in the coated glass fiber after drying and curing is less than 10 ppm or less than the detection limit of gas chromatography-mass spectrometry (GC-MS). Here, tertiary amines are understood to refer to compounds having a nitrogen atom, a lone pair of electrons, and three organic substituents. Even after the evaporation step, volatile tertiary amines may remain in the glass fiber. Therefore, in some embodiments, the coated glass fiber of the present invention contains at least 0.1 ppm, in some embodiments at least 0.2 ppm, or at least 0.3 ppm of tertiary amines. As indicated above, the amount of volatile tertiary amines in the coated glass fiber after drying and curing is preferably less than 10 ppm.
[0022] The thickness of the applied sizing is preferably 200 nm or less, more preferably 150 nm or less, more preferably 120 nm or less, more preferably 100 nm or less, and even more preferably 75 nm or less. It is understood that thinner sizing layers can be beneficial, especially for glass fibers having a diameter of less than 6 μm.
[0023] The sizing agent, which comprises a thermoplastic, resorbable and biocompatible polyester covalently bonded to the glass fiber through a coupling agent having at least one silane moiety, increases the strength of the interfacial bond between the glass fiber and the polymer matrix surrounding it after incorporation into a composite material. This effect can be quantitatively determined using a single fiber pull-out test. In this test method, single sized glass fibers are embedded in a molten polymer using a suitable device. The fibers are subsequently pulled out using a suitable device and the apparent interfacial shear strength is calculated. The method is described in detail below. The experiment can also be performed on fibers that are not coated with a compatibilizer. By comparing the results of fibers with and without a compatibilizer coating, a quantification of the effect of the compatibilizer coating on the peel force from the polymer matrix can be obtained.
[0024] In the present invention, the coated glass fiber has an apparent interfacial shear strength with a reference matrix polymer determined in a single fiber pull-out test, which is at least 10% higher than the apparent interfacial shear strength of a bare glass fiber with the same reference matrix polymer.
[0025] Within the context of this definition, a reference matrix polymer is a matrix polymer with a chemical composition that corresponds to that of the compatibilizer. For example, if the compatibilizer is polycaprolactone, the corresponding reference matrix polymer for this definition is polycaprolactone. This parameter therefore makes it possible to quantify the quality of adhesion of a sizing to the glass fiber relative to a standard matrix material, i.e. a polymer of the same composition as the compatibilizer. Within the context of this definition, a bare glass fiber is a coated glass fiber that has been baked at 500° C. for 2 hours in the presence of oxygen (usually air). This treatment removes the compatibilizer. By comparing the apparent interfacial shear strength values obtained for the coated and bare glass fibers with those of the standard matrix, it is possible to determine the effect of the sizing agent in the reference matrix.
[0026] Preferably, the coated glass fiber has an apparent interfacial shear strength with a reference matrix polymer that is at least 20%, in particular at least 30%, higher than the apparent interfacial shear strength of a bare glass fiber with the same reference matrix polymer, as determined in a single fiber pull-out test.
[0027] In one embodiment, the coated glass fiber has an apparent interfacial shear strength with a reference matrix polymer of at least 10 MPa, particularly at least 15 MPa, more particularly at least 20 MPa, as determined in a single fiber pull-out test. The apparent interfacial shear strength compared to a reference matrix polymer, as determined in the single fiber pull-out test, is preferably at least 30 MPa, more preferably at least 40 MPa, and even more preferably at least 50 MPa.
[0028] It should be noted that when the coated glass fibers are incorporated into other matrix materials, different values will be obtained in the single fiber pull-out test depending on the matrix-compatibilizer combination.
[0029] The (uncoated) glass fibers used in the present invention preferably have a diameter of less than 30 μm, particularly less than 25 μm, more particularly less than 20 μm, in some embodiments less than 15 μm, or even less than 10 μm, as determined according to ASTM D 1577-01C. Preferably, the diameter is at least 3 μm, particularly at least 5 μm, particularly at least 6 μm, or at least 8 μm. In one embodiment, the glass fibers are derived from a glass fiber bundle, and the coefficient of variation of the diameter of the glass fibers in the glass fiber bundle is 15% or less, particularly 10% or less. The coefficient of variation may be 8% or less, or 6% or less. In some embodiments, it has been found that the coefficient of variation may be 3% or less, which is a measure that indicates that the diameter is very uniform. The coefficient of variation is determined as follows: the diameter is determined for 30 glass fibers from the glass fiber bundle. The average diameter and the standard deviation are calculated. The coefficient of variation is the standard deviation divided by the mean diameter and is expressed as a percentage.
[0030] The glass fiber bundles used in the present invention preferably have at least 50 fibers, preferably at least 100 fibers, more preferably at least 150 fibers, even more preferably at least 200 fibers. As a maximum value, 5000 fibers, more particularly 3000 fibers, can be mentioned. The glass fiber bundles used in the present invention preferably have a linear density of 20 to 1300 tex, particularly 50 to 500 tex, preferably 70 to 300 tex, measured in accordance with ASTM D1577-01 A, throughout the bundle. The term "linear density" corresponds to the weight of a length of the glass fiber bundle, the unit tex corresponding to the weight in grams per 1000 meters of the fiber.
[0031] Glass is always composed of various components. They are often divided into three categories: 1) network formers, 2) network modifiers, and 3) intermediates. Network formers are a class of components that form the highly cross-linked skeletal network that is the main component of the glass and gives the glass most of its properties. Network modifiers are a class of components that can be added to fine-tune the physical properties of the glass to meet certain specifications. Network modifiers usually reduce the glass network connectivity. There are also components that participate in the glass network and from which the glass properties can be fine-tuned. These components belong to the intermediates class.
[0032] The glass fibers used in the present invention preferably have a composition comprising a network former and a network modifier, where the molar ratio of the network former to the network modifier is between 1 and 4, preferably between 1.5 and 3.5, more preferably between 2 and 3. It has been observed that a ratio according to such a range, in particular one of the preferred ranges, results in good glass quality, in particular suitable for fiber formation.
[0033] In a preferred embodiment, the glass fiber is a bioactive glass fiber. Bioactive glass fibers are known in the art and are designed to induce or modulate bioactivity. Bioactive materials are often surface-active materials that can interact with mammalian tissue. Bioactive glasses may further be designed to elute ions or other chemicals that result in osteoconductive, osteoinductive, anti-infective and / or angiogenic benefits.
[0034] The glass fibers are preferably made of oxides of silicon, such as silica (SiO), oxides of boron, such as diboron trioxide (B2O3) and boron suboxide (BO), and oxides of phosphorus, such as phosphorus trioxide (PO3) and phosphorus pentoxide (PO5 or PO4). 10 The glass fibers preferably contain a network former selected from the group consisting of oxides of sodium, such as Na2O or Na2O 2、 and a network modifier selected from oxides of magnesium, e.g., MgO, and oxides of calcium, e.g., CaO. More preferably, the glass fibres comprise some network formers and some network modifiers.
[0035] The glass fibers are preferably 50 to 75% by weight of SiO2, in particular 55 to 75% by weight, more in particular 60 to 75% by weight, 0-15% by weight of B2O3, 0.5 to 5% by weight of P2O5, in particular 0.5 to 4% by weight, more in particular 0.5 to 3% by weight, 5 to 20% by weight of Na2O, 0 to 25% by weight of CaO, in particular 2 to 25% by weight, more in particular 5 to 25% by weight, 0-10% by weight of MgO, 0-1 wt.% LiO, 0 to 15% by weight of K2O, in particular 0 to 10% by weight, more in particular 0 to 4% by weight, 0-4% by weight of SrO, 0-5 wt.% Al2O3, and 0-5% by weight Fe2O3 (not counting the sizing agent).
[0036] In one embodiment, the glass fiber has a composition including 60-75 wt.% SiO2, 0-15 wt.% B2O3, 0.5-3 wt.% P2O5, 5-20 wt.% Na2O, 5-25 wt.% CaO, 0-10 wt.% MgO, 0-1 wt.% Li2O, 0-4 wt.% K2O, 0-4 wt.% SrO, 0-5 wt.% Al2O3, and 0-5 wt.% Fe2O3 (not counting the sizing agent).
[0037] In one embodiment, the glass composition comprises less than 10 wt.%, in particular less than 5 wt.% B2O3. In one embodiment, the glass composition comprises 7-20 wt.% Na2O. In one embodiment, the glass composition comprises 2-8 wt.% MgO. In one embodiment, the glass composition comprises 5-15 wt.% CaO.
[0038] The glass fibers used in the present invention are preferably radiopaque, meaning that they are not transparent to X-rays. X-rays are understood to refer to high energy radiation having a wavelength of about 10 pm to about 10 nm. The use of radiopaque glass fibers is particularly attractive in composites for implantable medical devices, since it allows monitoring the degradation of the composite through X-rays in-vivo.
[0039] The glass fibres preferably have a tensile strength, measured by a tensile test according to DIN EN ISO 5079, of 1000 to 3000 MPa, preferably 1200 to 2500 MPa, more preferably 1400 to 2200 MPa.
[0040] The glass fibres preferably have a modulus of elasticity of 20 to 100 GPa, preferably of 35 to 85 GPa, more preferably of 50 to 70 GPa, measured by a tensile test according to DIN EN ISO 5079 "Determination of breaking force and elongation at break of individual fibres" (ISO 5079:2020).
[0041] Attractive glass fibers and glass fiber bundles for use in the present invention are described in a patent application having the same filing and priority date as this application, entitled "Resorbable and biocompatible glass fiber bundle having a well-defined diameter and process for making such," the text of which is incorporated herein by reference in its entirety.
[0042] The present invention also relates to a composite comprising a plurality of coated glass fibers according to the present invention, the plurality of coated glass fibers being embedded in a resorbable polymer matrix. The resorbable polymer matrix can be any suitable resorbable polymer matrix known in the art. Preferably, the resorbable polymer matrix is polylactic acid. Further examples will be given below.
[0043] The invention further relates to medical devices comprising the coated glass fibers or composites of the invention. Examples of medical devices are typically medical implants, including bone fixation devices, intramedullary nails, joint (hip, knee, elbow) implants, spinal implants, as well as other devices for such applications, such as fracture fixation, tendon reattachment, or spinal fixation.
[0044] Examples of bone fixation devices include screws, plates, rods, tapes, nails, wires, pins, tapes, anchors, cables, ties or wire ties, plate and screw systems, and external fixators.
[0045] The coated glass fibers or composites of the present invention can also be used in tissue engineering, such as in woven and nonwoven fabrics and scaffolds.
[0046] The present invention further provides a method for providing resorbable, biocompatible glass fibers coated with a sizing agent, comprising the steps of: a) glass fibers, a coupling agent having at least one epoxy moiety and at least one silanol group in a liquid medium; and a reaction product of the reaction of a compatibilizer with a volatile tertiary amine in a liquid medium, wherein the compatibilizer is a thermoplastic, resorbable and biocompatible polymer containing carboxylic acid end groups; coating the glass fibers with a sizing composition by contacting the glass fibers with a sizing composition; b) subjecting the coated glass fibers to a drying step; c) subjecting the dried coated glass fibers to a curing process at elevated temperature; d) subjecting the cured coated glass fibers to a step of evaporating the volatile tertiary amine. The method relates to the above-mentioned method, which comprises the steps of:
[0047] As used herein, the reaction product of a compatibilizer with a volatile tertiary amine, where the compatibilizer is a thermoplastic, resorbable, biocompatible polymer containing carboxylic acid end groups, may be referred to by the expression "neutralized compatibilizer." The term "neutralized" refers to the presence of ionic clusters containing negatively charged carboxylic acid groups and positively charged amine groups.
[0048] In step a) of the method according to the invention, the glass fibers are coated with a sizing composition by contacting the glass fibers with a coupling agent in a liquid medium and a neutralized compatibilizer in a liquid medium. In one embodiment, the coupling agent and the neutralized compatibilizer are present in a single liquid medium. In that case, step a) comprises coating the glass fibers in a liquid medium with a sizing formulation comprising a reaction product of a compatibilizer, the compatibilizer being a thermoplastic, resorbable and biocompatible polymer containing carboxylic acid end groups, with a volatile tertiary amine, and a coupling agent, the coupling agent having at least one epoxy moiety and at least one silanol group. In another embodiment, the coupling agent and the neutralized compatibilizer are provided in separate steps in individual liquid media. In that case, the glass fibers are generally first contacted with a liquid medium containing a coupling agent, and subsequently with a liquid medium containing the neutralized compatibilizer. Optionally, intermediate drying steps, and optionally intermediate curing steps, may be carried out. The contacting step can be carried out as known in the art, for example, by passing the fibers, for example in fiber bundle form, through a bath of the liquid medium.
[0049] The liquid medium is preferably an aqueous medium. In this case, the neutralized compatibilizer is present in the form of a dispersion, in particular a microdispersion, or even a nanodispersion. This dispersion can be formed by providing a compatibilizer containing an amount of a thermoplastic, resorbable and biocompatible polymer containing carboxylic acid moieties, neutralizing at least a portion of the carboxylic acid moieties of the compatibilizer with a certain amount of a tertiary amine, and dispersing the neutralized compatibilizer in a liquid medium, in particular an aqueous liquid medium. The compatibilizer can be provided, for example, in the form of a melt or in the form of a solution in a suitable solvent.
[0050] The tertiary amine used in the method of the present invention is selected so that it is volatile. In the context of this specification, the term "volatile" means that the amine can be evaporated from the glass fiber provided with the sizing agent. In addition, the tertiary amine used in the method is preferably selected so that it can act as a catalyst for the reaction between the coupling agent and the compatibilizer. Thus, preferably, the tertiary amine used in the method can act as a catalyst for the reaction between at least one epoxy moiety of the coupling agent and the carboxylic acid moiety of the compatibilizer.
[0051] After applying the sizing composition to the glass fibers, in one or two stages, with or without intermediate drying and / or curing as described above, the coated glass fibers are subjected to a drying step. In the drying step, the liquid medium, preferably water, is removed. Furthermore, if this has not already been done in the two-stage process described above, the silanol groups of the coupling agent react with the glass fibers and the resulting reaction water is also removed. The drying step is generally carried out under relatively mild conditions. This is because it is attractive to ensure the preservation of a portion of the tertiary amine that acts as a catalyst for the reaction of the terminal acid groups of the compatibilizer with the epoxy groups on the silane coupling agent. Suitable reaction conditions include temperatures in the range of 0 to 50° C. Preferably, the water is removed under reduced pressure (i.e. below 100 kPa, preferably below 50 kPa) and at about room temperature (i.e. 15 to 25° C.).
[0052] The silane moiety of the coupling agent creates hydrogen bonds with the -OH groups present on the glass fiber surface. This bond eventually transforms into a covalent bond with the glass fiber after losing a water molecule during the curing process. Therefore, the reaction between the epoxy moiety of the coupling agent and the glass is considered a solid-state reaction that results in the grafting of silane to solid glass via silanol bonds.
[0053] The dried coated glass fiber is subjected to a curing step at elevated temperature. As indicated above, in the curing step, the reaction between the silane moiety of the coupling agent and the -OH groups on the glass fiber surface is completed to form silanol bonds, and the reaction between the epoxy moiety of the coupling agent and the neutralized compatibilizer is carried out. This is preferably carried out above the glass transition temperature of the compatibilizer. Thus, the reaction between the epoxy moiety and the neutralized compatibilizer is preferably carried out at a temperature of at least 70°C, more preferably at least 80°C, more preferably at least 90°C, even more preferably at least 100°C. In order to prevent thermo-oxidative damage of the coupling agent and / or the compatibilizer, it may also be preferred to limit the temperature to a maximum of 140°C, more preferably at a maximum of 120°C. Thus, it is understood that the reaction between the epoxy moiety and the neutralized compatibilizer is preferably carried out at a temperature of 80-140°C, more preferably at least 100-120°C.
[0054] The coupling agent includes an epoxy (i.e., glycidyl) group for bonding to the carboxylic acid moiety. The coupling agent further includes a silanol group for bonding to the glass. In one embodiment, the silanol group is formed by reacting a compound having an alkoxysilane group with water (in a limited amount) to convert the alkoxysilane group to a silanol group. Preferred compounds having alkoxysilane groups are compounds selected from the group comprising 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltriethoxysilane, (3-glycidoxypropyl)trimethoxysilane, (3-glycidoxypropyl)methyldimethoxysilane, (3-glycidoxypropyl)trimethoxysilane, (3-glycidoxypropyl)methyldiethoxysilane, (3-glycidoxypropyl)dimethylethoxysilane, (3-glycidoxypropyl)triethoxysilane, 5,6-epoxyhexyltriethoxysilane, 2-(3,4-epoxycyclohexyl)ethylmethyldiethoxysilane, 1-(3-glycidoxypropyl)-1,1,3,3,3-pentaethoxy-1,3-disilapropane and 8-glycidoxyoctyltrimethoxysilane.
[0055] Preferably, the (neutralized) compatibilizer is dispersed in water as a nanodispersion.A nanodispersion is understood here to be a dispersion in which the droplets of compatibilizer in the continuous phase are nanometer scale, i.e., the D90 of the droplets of compatibilizer in liquid medium, measured using dynamic light scattering (e.g., using Malvern and ASTM E3247), is 350nm or less, preferably 250nm or less, more preferably 100nm or less, even more preferably 50nm or less, even more preferably 10nm or less.In one embodiment, the average particle size (z-average) of the neutralized compatibilizer in the liquid medium is 350nm or less, preferably 250nm or less, more preferably 100nm or less, even more preferably 50nm or less.
[0056] Moreover, it is observed that the presence of the tertiary amine successfully promotes dispersion of the compatibilizer, a process that is speculated to work by converting a portion of the compatibilizer into a transient ionic surfactant that promotes dispersion by preferentially locating at the water-polymer interface.
[0057] Preferably, the molar ratio of the tertiary amine to the carboxylic acid moiety is from 0.4 to 2.0, preferably from 0.5 to 1.0, more preferably from 0.6 to 0.8.
[0058] The compatibilizer is preferably selected from the group consisting of polylactide (PLA), poly-L-lactide (PLLA), poly-DL-lactide (PDLA), L-lactide / DL-lactide copolymer (PLDLA), polyglycolide (PGA), poly(ε-caprolactone) (PCL), copolymers of glycolide, copolymers of ε-caprolactone, copolymers of lactide, glycolide / trimethylene carbonate copolymer (PGA / TMC), lactide / tetramethylglycolide copolymer, lactide / trimethylene carbonate copolymer, lactide / δ-valerolactone copolymer, lactide / ε-caprolactone copolymer, glycolide / lactide copolymer (PGLA), lactide / glycol ... In one embodiment, the compatibilizer is selected from the group consisting of ethylenediamine / trimethylene carbonate terpolymer, lactide / glycolide / ε-caprolactone terpolymer, PLA / polyethylene oxide copolymer, asymmetric 3,6-substituted poly-1,4-dioxane-2,5-dione, polyhydroxybutyrate (PHB), PHB / β-hydroxyvalerate copolymer (PHB / PHV), poly-β-hydroxypropionate (PHPA), poly-p-dioxanone (PPD), poly-δ-valerolactone-poly-ε-caprolactone, poly(ε-caprolactone-DL-lactide) copolymer, polyesters of oxalic acid, poly-β-malic acid (PMLA), poly-β-alkanoic acid, and mixtures thereof. Additionally or alternatively, the compatibilizer has a number average molecular weight (M) of 50 kg / mol or less, preferably 35 kg / mol or less, more preferably 30 kg / mol or less, and even more preferably 25 kg / mol or less. n). The compatibilizer preferably has a molecular weight of at least 2.0 kg / mol, in particular at least 3.0 kg / mol. The appropriate weight of the compatibilizer in each case also depends on the nature of the compatibilizer. The molecular weight of these polymers was measured via relative GPC analysis using polystyrene calibration, as detailed in the examples. The compatibilizer is preferably selected from the group of polylactide, poly(lactide-co-glycolide), poly(lactide-co-ε-caprolactone), polyglycolide (PGA) and poly(ε-caprolactone) (PCL). Further preferred compatibilizers include hydrophilic polyester copolymers based on polyethylene glycol monomers, in particular copolymers of polyethylene glycol with lactide, glycolide and / or caprolactone.
[0059] The tertiary amine is preferably selected from the group comprising trimethylamine, triethylamine, tripropylamine, tributylamine, ethyldimethylamine, methyldiethylamine, dimethylethanolamine, diethylethanolamine, N'-methylmorpholine, N'-ethylmorpholine, pyridine, 2-methylpyridine, 3-methylpyridine, 4-methylpyridine and 2,6-lutidine.
[0060] Preferably, at least a portion of the tertiary amine is removed under reduced pressure (ie, less than 100 kPa, preferably less than 50 kPa) and at elevated temperature (80-140° C.).
[0061] Preferably, the compatibilizer is in a molten state or dissolved in an organic solvent when combined with the tertiary amine to form a dispersion of the neutralized compatibilizer in a liquid medium.
[0062] The compatibilizer may preferably be provided with carboxylic acid moieties by converting alcohol moieties of a thermoplastic, resorbable and biocompatible polymer to carboxylic acid moieties by ring-opening reaction with an anhydride and / or by synthesizing the polymer from a suitable cyclic ester monomer (or a suitable mixture of such monomers) and an α-hydroxy acid initiator. Alternatively, compatibilizers with acid groups may be prepared by polycondensation of diacids and diols with a slight excess of acid, according to methods described in the art of polymer chemistry.
[0063] Preferably, the molar ratio of coupling agent to the amount of carboxylic acid moiety is at least 0.5. In other words, preferably, at least two carboxylic acid moieties are provided for each silane moiety. The greater the number of carboxylic acid moieties, the greater the chance that they will reach and chemically bond to the glass fiber.
[0064] The present invention further provides a kit of parts for coating a resorbable, biocompatible glass fiber, comprising: a compatibilizer comprising an amount of a thermoplastic, resorbable and biocompatible polymer containing a carboxylic acid moiety; Volatile tertiary amines, and Coupling agents having at least one epoxy moiety and at least one silane moiety The above-mentioned kit of parts includes:
[0065] Preferably, the kit is a medical kit, in which case it is understood that the kit is intended and suitable for producing a medical device.
[0066] Preferably, the kit further comprises resorbable, biocompatible, preferably bioactive, glass fibres.The kit of parts may further comprise instructions for carrying out the method according to the invention.
[0067] As indicated above, the present invention also relates to a composite comprising the coated glass fiber of the present invention and a resorbable and biocompatible polymer matrix. Examples of suitable resorbable and biocompatible polymer matrix materials are polylactide (PLA), poly-L-lactide (PLLA), poly-DL-lactide (PDLA), L-lactide / DL-lactide copolymer (PLDLA), polyglycolide (PGA), poly(ε-caprolactone) (PCL), copolymers of glycolide, copolymers of ε-caprolactone, copolymers of lactide, glycolide / trimethylene carbonate copolymer (PGA / TMC), lactide / tetramethylglycolide copolymer, lactide / trimethylene carbonate copolymer, lactide / δ-valerolactone copolymer, lactide / ε-caprolactone copolymer, glycolide / lactide copolymer (PGLA), lactide / trimethylene carbonate ... The polymers include polymers selected from the group including poly(phenylene oxide), ... With regard to the compatibilizer, the polymer matrix is preferably selected from the group of polylactide, poly(lactide-co-glycolide), poly(lactide-co-ε-caprolactone), polyglycolide (PGA), and poly(ε-caprolactone) (PCL).
[0068] In one embodiment, the compatibilizer and the polymer matrix are constructed from the same types of monomers, more particularly in the same ratios, which ensures good compatibility between the coated glass fibers and the matrix.
[0069] In one embodiment, at least 10% of the structural units of the compatibilizer are identical to the structural units of the matrix polymer. This is one way to ensure good compatibility between the glass fiber and the matrix material. In one embodiment, at least 20%, at least 40%, or at least 60% of the structural units of the compatibilizer are identical to the structural units of the matrix polymer. In one embodiment, both the compatibilizer and the matrix polymer contain at least 20% by weight, particularly at least 30% by weight, of lactide units. In one embodiment, both the compatibilizer and the matrix polymer contain at least 20% by weight, particularly at least 30% by weight, of caprolactone units. In another embodiment, the compatibilizer and the matrix polymer contain at least 20% by weight, particularly at least 30% by weight, of glycolide units.
[0070] Preferably, the intrinsic viscosity of the matrix polymer in the composite material is 1.5 to 4.0 dL / g, preferably 1.8 to 3.0 dL / g, more preferably 2.0 to 3.0 dL / g.
[0071] Generally, the polymer composite material has a Young's modulus (tested by ASTM D7264 / D7264M) higher than the matrix polymer, preferably between 110% and 1000%, more preferably between 200% and 600%, and most preferably between 300% and 500% compared to the matrix polymer.
[0072] Preferably, the glass reinforced polymer composite material has a mechanical strength according to a three-point bend test (tested according to ASTM D7264 / D7264M) that is higher than the strength of the matrix polymer, preferably at least 110% compared to the matrix polymer, preferably at least 200% compared to the matrix polymer, and most preferably at least 400% compared to the matrix polymer when the applied force is perpendicular to the reinforcing fibers.
[0073] Preferably, the composite has a glass fiber content, calculated on glass and polymer combined, of 5-95%, preferably 10-90%, more preferably 15-80%, even more preferably 20-70%, and most preferably 30-60% by weight. Alternatively, the composite preferably has a glass fiber content of at least 60%, more preferably at least 70%, even more preferably at least 80%, and even more preferably at least 90% by weight.
[0074] The composite according to the invention may contain, in addition to the glass fibers and the polymer, further components, for example up to 30% by weight, up to 20% by weight, or up to 10% by weight. Examples of further components may be hydroxyapatite and calcium phosphates, such as tricalcium phosphates (TCP), e.g. β-TCP. It may be preferred that the composite contains an additive, such as an active pharmaceutical ingredient (API) or a mineral component, embedded within the composite.
[0075] The present invention also relates to a medical device comprising a coated glass fiber according to the present invention in a polymer matrix as described above or a composite according to the present invention. An attractive composite and a method for its manufacture are described in a patent application entitled "Biocompatible and resorbable polymer composite material and method for obtaining such" having the same applicant, inventor and filing date as the present application, the text of which is incorporated herein by reference in its entirety.
[0076] As the skilled person knows, glass fibers are generally produced in the form of fiber bundles, where a plurality of individual fibers, often also referred to as filaments, are obtained as a bundle from the glass manufacturing process. The fiber bundles may also be referred to as yarns or strands. The present invention relates to coated glass fibers and to a method of coating glass fibers. The coating procedure may often be applied to the glass fibers in the glass fiber bundles, but proper distribution of the fibers will ensure that the coating is applied to the individual fibers. The coated glass fibers may be incorporated into a composite. In the composite, the glass fibers or glass fiber bundles may be present as continuous fibers and / or chopped fibers. When chopped fibers are used, they generally have a length in the range of 1 mm to 50 mm, in particular 1 mm to 25 mm, more in particular 1 mm to 20 mm, even more in particular 2 mm to 10 mm, and most in particular less than 4 mm and more than 1 mm.
[0077] In one embodiment, the medical device comprises a unidirectional composite tape. Glass fiber-based tapes are known in the art. They comprise a biodegradable polymer and a plurality of continuous glass fibers aligned in one direction, where the fibers are aligned along the length of the tape. The tape generally has a width of at least 2 times, particularly at least 5 times, more particularly at least 10 times, the thickness of the tape. The length of the tape generally is at least 10 times, particularly at least 100 times, the width of the tape. The thickness of the tape is preferably less than 0.3 mm, more preferably less than 0.2 mm, even more preferably less than 0.15 mm. The length of the tape is preferably at least 1 m, more preferably at least 5 m, even more preferably at least 10 m. The third dimension (i.e., width) is preferably 0.5 to 10 cm, more preferably 0.8 to 5 cm, even more preferably 1 to 2.5 cm. A composite tape can be obtained, for example, by spreading the fibers of a glass fiber bundle, contacting the glass fibers with a polymer matrix in a liquid phase and solidifying the matrix. The unidirectional composite tape preferably has a matrix content of 2-40% by weight, in particular 5-30% by weight, more in particular 5-25% by weight, in a particular embodiment 10-20% by weight. As regards the nature of the matrix and the nature of the glass fibers, the preferred embodiments mentioned elsewhere also apply here.
[0078] In one embodiment, the medical device comprises multiple layers, where one or more layers comprise one or more composite tapes.
[0079] Thus, in one embodiment, the composite is molded in the form of a unidirectional composite tape, as described above. In alternative embodiments, the composite is molded as strands, (cannulated) rods, tubes, pellets, or granules. Strands / rods are fiber-reinforced polymers, preferably of round shape with a diameter of 5 to 50 mm. Pellets are small sections of the length of the rod with a diameter of about 5 to about 50 mm, and granules are small particles with a diameter of about 1 to about 10 mm. The dimensions of the pellets or granules may be adapted to match the dimensions of the feed screw used in polymer processing techniques, such as injection molding.
[0080] As will be clear to those skilled in the art, different embodiments of the present invention can be combined as long as they are not mutually exclusive. The preferred aspects regarding the properties and sizing of the various components of the glass fiber also apply to the kit of parts, the composite, and the medical device.
[0081] All percentages used herein are by weight unless otherwise specified.
[0082] When amounts, concentrations, dimensions, and other parameters are expressed in the form of ranges, preferred ranges, upper values, lower values, or preferred upper and lower values, it is to be understood that any range that can be obtained by combining any upper value or preferred value with any lower value or preferred value is also specifically disclosed, regardless of whether the resulting range is expressly stated in the context.
[0083] The present invention will now be illustrated with reference to the following examples, without being limited thereto or by them.
[0084] Working Example
[0085] analysis technology
[0086] Acid number (AN): Acid number (AN) is the amount of potassium hydroxide (KOH) in mg required to neutralize the free acid in 1 g of compatibilizer and was determined via titration using a Metrohm 876 Dosimat Plus equipped with a Metrohm 801 stirrer. Samples were prepared by weighing 0.5 g of polymer into a 250 mL Erlenmeyer flask followed by the addition of 100 mL of pre-neutralized DCM / methanol (4 / 1 vol.%) mixture. After complete dissolution, three drops of a 1 wt.% phenolphthalein solution in ethanol were added and the mixture was titrated with 0.1 M ethanolic KOH until a pink color was obtained that persisted for at least 15 seconds. The amount of KOH required in mL (a) was recorded and the acid number was calculated according to the following formula:
number
[0087] Relative Gel Permeation Chromatography (GPC): A gel permeation chromatograph (Agilent 1200 series) was used to measure the relative number average and weight average molecular weights (M, respectively) of the compatibilizers against polystyrene standards. n and M w ) was used to measure the solubility of the amines. The GPC consisted of a guard column, two PL gel mixed D columns, and an evaporative light scattering detector (ELSD). Ethanol-stabilized HPLC grade chloroform (Biosolve) was used as the mobile phase at a flow rate of 1 mL / min, and the measurements were performed at 35°C. 15 mg of the compatibilizer sample was dissolved in 15 mL of chloroform and then filtered through a 0.45 μm filter before GPC analysis. The GPC system was calibrated using narrow polystyrene standards.
[0088] Headspace GC-MS method for TEA quantification: 100 mg of the coated glass fiber was extracted with dimethyl sulfoxide (DMSO) containing deuterated triethylamine (d-TEA) as an internal standard. Imidazole was added to the DMSO to release the TEA from the compatibilizer. The sample was incubated at 100°C for 20 minutes and then analyzed using a headspace GC-MS instrument. The column used was a TG-624 (30 m x 0.25 mm x 1.40 μm) and helium was used as the carrier gas.
[0089] A calibration curve for TEA was prepared using the same internal standard as the samples. Results were normalized to the polymer content on the glass fiber measured by ignition technique. Quantification by GC-MS was performed in duplicate for each sample.
[0090] Particle size of nano dispersion: The particle size was measured using dynamic light scattering using a Malvern ZetaSizer nano. Tests were performed on diluted aqueous samples in disposable plastic cuvettes according to the ASTM E3247 method. At least three measurements were made for each sample and the average value was reported. D90 values were determined by this method.
[0091] Moisture content quantification: The coulometric Karl-Fisher titration method was used to determine the water content of glass sized samples. The important parameters were the sample weight and the vial temperature. The tests were carried out at a sample weight of 0.1 ± 0.01 grams and a temperature of 130°C.
[0092] Loss on ignition method: The loss on ignition (LOI) technique is a suitable technique for determining the sizing agent content for glass fiber samples. The sizing agent content of 1±0.2 g samples was determined in a LECO 701 macro thermogravimetric analyzer (TGA). The test began by recording the sample in the software, followed by determining the initial (empty) crucible weight (with lid). Once the initial weight was measured, the samples were added to the crucibles in their respective positions, and the equipment determined the weight of the samples. The instrument was subsequently heated to 110° C. and maintained for 30 minutes. After 30 minutes, the equipment was heated to 565° C. at a rate of 25° C. / min and held at that temperature for 2 hours. Weights were determined at regular intervals while the instrument was running, and the percent mass loss for each step was calculated and reported. The first step (110°C) measured the moisture in the sample without burning off any sizing from the fiber. At the higher temperature (565°C), the dry sizing content was obtained by burning off the sizing on the glass fiber.
[0093] Single fiber pull-out test method for measuring interfacial shear strength (IFSS) Single fibers were separated from the glass fiber bundle by immersing the bundle in acetone. A portion of the same fiber was used to measure fiber diameter. Another portion was embedded in polymer with TextTechno FimaBond. Polymer granules were melted in an aluminum crucible at 270°C for 5 minutes. While the polymer was melting, a single fiber was inserted into a hollow needle placed directly above the crucible containing the polymer. When the polymer was completely melted, the fiber was lowered into the center of the molten polymer mass and contacted the polymer. The fiber was then embedded in the molten polymer with an embedment depth of 220 microns. The polymer was then held at 150°C for an additional minute to allow for chain entanglement, and then cooled to room temperature. The sample was removed from FimaBond and placed upside down in a Favimat equipped with a FimaTest fiber pull-out fixture. The Favimat was equipped with a highly sensitive 210cN load cell. The fibers were gripped with rubber grips next to the polymer and pulled at 0.6 mm / min. The test was performed at ambient temperature. The test was stopped when the force dropped to zero and the apparent interfacial shear strength (IFSS) was automatically calculated by the software based on the fiber diameter, embedment depth and maximum force. At least 10 samples for each fiber group were tested and the average value is reported.
[0094] Example 1: Synthesis of Carboxylic Acid Functionalized Poly(lactide / ε-caprolactone) 75 / 25 (molar ratio) (compatibilizer)
[0095] A mixture of L-lactide (3.50 mol) and ε-caprolactone (1.17 mol) was bulk polymerized using stannous 2-ethylhexanoate as catalyst and 1,4-butanediol (0.2 mol l) as initiator. The resulting poly(lactide / ε-caprolactone) diol was acid functionalized by subsequent reaction with succinic anhydride (0.44 mol). Residual monomer was removed by ultrafiltration. The final polymer was amorphous (Tg=18° C.) and had a weight average molecular weight (Mw) of 5.6 kg / mol and a number average molecular weight (Mn) of 3.6 g / mol (both determined by GPC against polystyrene standards) and an acid number of 26.9 mg KOH / g polymer. The residual amount of Sn determined via ICP was 140 ppm.
[0096] In a similar manner, compatibilizers having different molecular weights and acid numbers were prepared and their properties are summarized in Table 1 below.
[0097] [Table 1]
[0098] Example 2: Preparation of a Dispersion of Compatibilizer in Water
[0099] Dispersions of the compatibilizer in water can be prepared using solvent assisted or melt dispersion methods.
[0100] (a) Solvent-assisted method Poly(lactide / ε-caprolactone) 75 / 25 (molar ratio) initiated with 1,4-butanediol and end-capped with succinic anhydride was dissolved in acetone (43 wt%). The copolymer was neutralized by adding triethylamine (0.6 moles TEA / mole COOH). The neutralized copolymer was added to Milli-Q water at about 20° C., and the acetone was gently removed under vacuum. A bluish dispersion (about 20 wt%) with a particle size (D90) of 100 nm was obtained (measured via dynamic light scattering using a ZetaSizer-nano according to ASTM E3247).
[0101] (b) Melt dispersion method A dispersion of the compatibilizer in water was obtained by melting a 75 / 25 (molar ratio) poly(lactide / ε-caprolactone) starting with 1,4-butanediol and end-capped with succinic anhydride (acid number: 26.9 mg KOH / g polymer) at 90° C. and adding triethylamine (0.9 mol TEA / mol COOH) to the polymer. After the mixture was stirred for 5 minutes, Milli-Q water preheated at 50° C. was added and stirring was continued until a bluish dispersion (approximately 20 wt%) with a particle size (D90) of 260 nm was obtained.
[0102] Example 3: Effect of neutralization degree
[0103] This experiment illustrates the effect of the degree of neutralization on the final properties of the nanodispersion (aqueous). 9 grams of acid functionalized random poly(lactide / ε-caprolactone) of 75 / 25 molar ratio with an acid value of 31.1 mg KOH / g was dissolved in 200 mL of acetone. After complete dissolution, a certain amount of TEA was added. The solution was subsequently stirred for 30 minutes at ambient temperature in a closed vessel for neutralization purposes. The solution was then gradually added to 200 mL of Milli-Q water under stirring. The resulting dispersion was stirred in an open beaker in a fume hood for about 24 hours until all the acetone had evaporated and about 5 wt% of polymer remained in the water. The particle size was measured using a Malvern Zeta sizer nano. Table 2 below summarizes the particle size of the resulting dispersions at different degrees of neutralization (0.4, 0.5, 0.6, 0.7 and 1 mole of TEA per mole of acid).
[0104] [Table 2]
[0105] Example 3a: Preparation of a Dispersion in the Absence of TEA
[0106] The procedure of Example 3 was repeated, except that no TEA was added to the polymer solution. As in Example 3, the polymer solution was slowly added to 200 mL of Milli-Q water under stirring. The resulting dispersion was stirred in an open beaker in a fume hood for about 24 hours until all the acetone had evaporated and about 5 wt.% polymer remained in the water. The polymer was not in the form of a nanodispersion. Rather, large particles formed that aggregated and settled to the bottom of the container. The PSD (D90) was estimated to be on the order of tens to hundreds of microns, which could not remain suspended and therefore could not be measured via a DLS (Dynamic Light Scattering) instrument such as the ZetaSizer-nano.
[0107] Example 4: Effect of molecular weight
[0108] Acid-functionalized random poly(lactide / ε-caprolactone) copolymers (compatibilizers 2, 3, 4 and 5 from Example 1) with a molar ratio of 75 / 25, various molecular weights and corresponding acid values were dissolved in acetone at 5 wt%, followed by the addition of triethylamine at a molar ratio of 1:1 to the acid. After stirring the solution for 30 minutes, the polymer solution was gradually added to purified Milli-Q water. After evaporating the acetone in a fume hood for 24 hours, a 5 wt% aqueous polymer dispersion was obtained. The particle size (D90) was measured by DLS (ZetaSizer). Table 3 below provides the molecular weight data, acid value data and particle size data.
[0109] [Table 3]
[0110] Example 5: Sizing synthesis and testing
[0111] An acid functionalized poly(lactide / ε-caprolactone) copolymer with 75 / 25 mol%, Mn 5 kg / mol and Mw 8 kg / mol (measured by relative GPC) was dissolved in acetone to prepare 10% (w / w). The acid value of the copolymer was 32.5 mg KOH / g. Upon complete dissolution, triethylamine (TEA) was added to the vessel in a 1:0.6 carboxylic acid / TEA molar ratio to neutralize the acid. The neutralized polymer solution was gradually added to Milli-Q water (same amount as acetone) while stirring with a mixer. The acetone was evaporated off by applying vacuum (-15 to -20 in Hg) for at least 7 hours or until all the acetone was removed. At this time, it was assumed that all the acetone was removed from the system and a solid content of more than 10% was achieved. This resulted in an aqueous dispersion with D90<350 nm and pH less than 7.8. The dispersion was then mixed with hydrolyzed silane (3-glycidyloxypropyltriethoxysilane) to achieve a molar ratio of 0.5 relative to the acid in the final sizing solution to achieve 5% by weight solids in the sizing agent.
[0112] The above sizing agent was then applied via a kiss roller onto freshly drawn glass fibers with a target composition of 67.8 wt% SiO, 51.5 wt% P2O, 2.3 wt% B2O, 9 wt% CaO, 5.4 wt% MgO, and 14 wt% Na2O formed in a melt spinning process, and the fibers were wound onto a core for further processing.
[0113] The wet glass fiber cake was dried under air flow for 24 hours, followed by drying under vacuum (p=0.66 kPa) for 24 hours. The moisture content was less than 1000 ppm and the TEA content was 3448 ppm, which corresponds to a molar ratio of TEA / COOH of 0.05 or 1:20. The drying process promoted the reaction of silanol groups with the glass.
[0114] The fiber cake was then cured at 90°C for 16 hours to promote the reaction of the acid end groups of the compatibilizer with the epoxy groups. After curing, it was subjected to deep vacuum at 90°C for 2 hours to remove the remaining TEA. The sizing agent content determined by loss on ignition TGA method was 1.2 wt%. The amount of TEA was quantified and found to be 2 ppm on the coated glass fiber.
[0115] Example 6: Grafting efficiency
[0116] Depending on the manufacturing process of the composite, different amounts of sizing agent may be required. For a sizing that is compatible with a thermoplastic matrix polymer, it may be preferable to have at least a monolayer of sizing agent. For a given glass diameter and a specific molecular weight compatibilizer, the amount of this monolayer can be calculated as a weight percentage of glass. For a glass fiber filament with a diameter of 12 microns and a compatibilizer with a Mn of 3 kg / mol, the calculated amount of sizing agent to form a covalently bonded monolayer on the glass fiber with the aid of an epoxy silane is about 0.3 wt.% of the glass fiber. This calculation also indicates that the silanol bonds available for reaction with the epoxy silane are 4.6 OH / nm. 2 This means that the average density of silanols in amorphous silica is typically about 4.8 OH / nm 2 The assumption is based on literature suggesting that the covalently attached sizing agent does not wash off with acetone.
[0117] To confirm the grafting of the sizing agent onto the glass fiber, the sized fibers obtained according to the procedure described in Example 5 were immersed in acetone for 10 minutes and then further washed with clean acetone two more times to remove the remaining unreacted compatibilizer. The samples were dried and analyzed for sizing agent content via loss on ignition technique using a LECO macro TGA 701. The sizing agent content on the glass fiber before washing was 0.94 wt.%, while the sizing agent content after washing off the unreacted sizing agent from the glass fiber was approximately 0.39 wt.% of the glass fiber. This experiment confirmed the presence of a monolayer of sizing agent covalently bonded to the glass fiber surface. Excess and unreacted sizing agent serves to hold the fibers together in the glass fiber bundle and protects the fibers from abrasion during the fiber winding and composite manufacturing process.
[0118] Example 7: Effect of compatibilizer
[0119] Adhesion strength was measured directly using a single fiber pull-out method. A glass fiber was first treated with a silane and cured. The treated glass fiber was then coated with a coating containing the compatibilizer used in Example 5, followed by a curing step to react the compatibilizer with the silane. A single glass fiber filament was then embedded in the matrix polymer (Purasorb PLDL 7030) and pulled using a Fimatest fixture in a Favimat machine. A glass fiber treated with silane only was used as a negative control.
[0120] It was found that the apparent interfacial shear strength (IFSS) for the silane treated fiber was 36±17 MPa, which jumped to 42±15 MPa for the fiber coated with a PLC compatibilizer with a calculated Mn=3 kg / mol. Further improvement was seen for glass fibers coated with PLC compatibilizers formulated to have calculated Mn values of 13 kg / mol and 17 kg / mol, with IFSS measured at 51±9 MPa and 53±8 MPa, respectively.
[0121] Example 8 - Applying a sizing agent having polycaprolactone as a compatibilizer to glass fibers and incorporating the coated fibers into a polycaprolactone matrix to form a polycaprolactone glass fiber reinforced composite material which is further processed to form a composite plaque.
[0122] 1. Preparation of Silane-treated Glass Fibers The hydrolyzed silane solution was prepared by dissolving 117 g of 3-glycidyloxypropyltriethoxysilane in 10 kg of ASTM Type II purified water at 50° C. for 90 minutes. The hydrolyzed silane solution was then applied in-line via a kiss roller onto freshly drawn glass fibers as they were formed in the melt spinning process. The glass composition was the same as that applied in Example 5. The resulting fiber bundle was wound onto a core for further processing. The wet glass fibers were air-dried and then vacuum-dried at room temperature to bring the moisture level to less than 1000 ppm. The dried glass fibers were heat-treated at 90° C. for 4 hours to covalently bond the silane to the hydroxyl groups on the glass fiber surface.
[0123] 2. Preparation of aqueous PC(IV 0.15) nanodispersion 40 g of acid functionalized polycaprolactone with IV of 0.15 dL / g (measured according to ASTM 2857) and acid value of 39.4 mg KOH / g was dissolved in 1600 g of acetone for 1 hour. After complete dissolution, triethylamine (TEA, from Sigma Aldrich) was added in a 1:1 molar ratio to the acid to neutralize the acid end groups. After stirring for 15 minutes, the polymer solution was gradually added to ASTM Type II purified water. After 24 hours of evaporation to remove the acetone, an aqueous nanodispersion with a solid content of about 3 wt% was obtained. The average particle size (z-average) measured by DLS (Malvern ZetaSizer-nano) was found to be 37 nanometers, with a D90 of 39 nm.
[0124] 3. Preparation of sized glass fibers of PC(IV 0.15) The silane-treated glass fibers (having an average diameter of 16 microns) obtained in step 1 above were further treated with the compatibilizing polymer (PC, IV 0.15 dL / g) prepared in step 2 above by passing them in a continuous manner through a polymer nanodispersion bath in an off-line reel-to-reel sizing applicator system. The line speed was 5 m / min. The sized fibers were collected on another perforated stainless steel (SS) core. Subsequently, the fibers were vacuum dried at room temperature and then cured at 90° C. for 16 hours to promote the reaction between the acid end groups of the compatibilizer and the epoxy groups of the silane already covalently bonded to the glass surface. The TEA present at the reaction sites acted as a catalyst and was finally removed by applying a vacuum.
[0125] Once cured, the PC-sized glass fiber samples were tested for the presence of a sizing layer that was a PC (IV 0.15) compatibilizer via the TGA loss-on-ignition method. The results confirmed the presence of 1±0.5 wt.% sizing on the glass fibers.
[0126] 4. Preparation of Composite Tapes Comprising Polycaprolactone Polymer and Fibers Sized with Polycaprolactone Compatibilizer A 10 wt% solution of high molecular weight polycaprolactone (Purasorb PC17, IV 1.7 dL / g, commercially available from Corbion Purac) was prepared in acetone at 50°C. A bundle of sized PC fibers (576 filaments) obtained in step 3 was coated with polymer by passing it through a polymer solution bath with a continuous reel-to-reel applicator system. The polymer solution bath was equipped with rollers and pins to spread the fibers for better wetting. The solvent was removed by passing the coated fibers through an anti-solvent (ethyl alcohol) bath at room temperature with a line speed of 2 m / min, followed by air drying for 24 hours. After drying, the polymer-coated fibers appeared as a thin and narrow tape. The coated and dried fibers were analyzed for fiber / polymer content via a LECO, TGA701 heat loss method. The polymer content was 14.2% by weight.
[0127] 5. Composite plaques obtained by compression molding a composite containing polycaprolactone and coated glass fibers The composite tapes obtained in step 4 above were cut into long strips of 100 mm length, and a certain amount was stacked in a uniform direction and spread into the cavity of a preheated mold to prepare samples for mechanical testing. On the coated fiber stack, an additional polymer (Purasorb PC17, Tm 60°C) film was added as a top layer to make 50 wt% of the fiber in the final molded part. The mold cavity was 100 mm x 100 mm x 1 mm. These coated fiber bundles and polymer film layers were then heated above the softening temperature of the polymer, pressed, and subsequently cooled and removed from the mold. Composite plaques were obtained and used for analytical purposes.
[0128] 6. Mechanical Testing of the Composite The composite plaques from step 5 above were cut into rectangular coupons (50x13x1mm; LxWxT) and subjected to flexural property testing (3-point-bending test) according to ASTM D7264 / D7264M-15 using a Lloyd universal mechanical tester equipped with a 3 point bend fixture and a 2.5 kN load cell. A span to thickness ratio of 16:1 was used. With a standard width of 13 mm, the length of the specimen was approximately 20% longer than the support span (10% on each side). The average strength for the six samples tested was 147±7.6 MPa (a 600% improvement over the base polymer strength of 23 MPa) and elastic modulus was 6.46±0.68 GPa (a 58-fold improvement over the base polymer strength of 110 MPa). The samples tested were analyzed for fiber content via TGA heat loss method and the average fiber content of the composite was found to be 50.4 wt%.
[0129] Example 9 - Providing glass fibers with poly(DL-lactide) (PDL) as a compatibilizer and incorporating the coated fibers into a poly(DL-lactide) matrix to form a poly(DL-lactide) glass fiber reinforced composite material which is further processed to form a composite plaque.
[0130] Epoxy-functional, silane-treated glass fibers were prepared as described in Example 8 above.
[0131] 30 g of acid functionalized poly(DL lactide) (50 / 50) polymer with IV of 0.4 dL / g and acid value of 4.1 mg KOH / g was dissolved in 1500 g of acetone for 1 hour. After complete dissolution, TEA was added at a molar ratio of 1:1.3 to the acid to neutralize the acid end groups. After stirring the solution for 15 minutes, the polymer solution was slowly added to ASTM Type II purified water. After 24 hours of evaporation to remove the acetone, an aqueous dispersion of about 3 wt% was obtained. The average particle size (z-average) measured by DLS (Malvern ZetaSizer-nano) was found to be 30 nanometers, with a D90 of 24 nm.
[0132] The silane-treated glass fibers were further treated with compatibilizing polymer in an off-line reel-to-reel sizing applicator system by passing the glass fiber bundle through a bath of the above-mentioned polymer nano-dispersion in a continuous manner. The line speed was 5 m / min. The sized fibers were collected on another perforated SS core. The fibers were vacuum dried at room temperature and then cured at 90°C for 16 hours to promote the reaction of the -COOH end groups of the compatibilizer polymer with the epoxy ends of the silanes already covalently bonded to the glass surface. The TEA present at the reaction sites acted as a catalyst and was finally removed by applying a vacuum.
[0133] Once cured, the glass samples were tested for the presence of a sizing layer via the TGA loss on ignition method, and the results confirmed the presence of 1±0.5% sizing by weight on the glass fibers.
[0134] A 10 wt% solution (IV 2.0 dL / g) of high molecular weight poly(DL lactide) was prepared in acetone. A bundle (576 filaments) of the above sized fibers (having an average diameter of 16 microns) was coated with high molecular weight poly(DL lactide) by passing it through a polymer solution bath with a continuous reel-to-reel applicator system. The polymer solution bath was equipped with rollers and pins to spread the fibers for better wetting. The solvent was removed by passing the coated fibers through an antisolvent (ethyl alcohol) bath at room temperature. The line speed was 1 m / min. The coated fibers were air-dried for 24 hours. After drying, the coated fibers appeared as a thin and narrow tape. The coated and dried fibers were analyzed for fiber / polymer content via a LECO TGA701 heat loss method. The polymer content was 15.4 wt%.
[0135] The resulting composite tapes were cut into long strips of 100 mm length, and a certain amount was stacked in a uniform direction and spread into the cavity of a preheated mold to prepare samples for mechanical testing. On the coated fiber stack, an additional polymer (Purasorb PLDL7020) film was added as a top layer to make 50 wt% fiber in the final molded part. The mold cavity was 100 mm x 100 mm x 1 mm. These coated fiber bundles and polymer film layers were then heated above the softening temperature of the polymer, pressed, and subsequently cooled and removed from the mold. Composite plaques were obtained and used for analytical purposes.
[0136] The composite plaques were then cut into rectangular coupons (50x13x1 mm; LxWxT) and subjected to bending property testing (3-point-bending test) according to ASTM D7264 / D7264M-15 using a Lloyd universal mechanical tester equipped with a 3 point bend fixture and a 2.5 kN load cell. A span to thickness ratio of 16:1 was used. With a standard width of 13 mm, the length of the specimen was approximately 20% longer than the support span (10% on each side). The average strength for the six samples tested was 491.3±38.6 MPa (446% improvement from the base polymer's strength of 110 MPa) and elastic modulus was 12.72±1.5 GPa (374% improvement from the base polymer's strength of 3.4 GPa). The samples tested were analyzed for fiber content via TGA heat loss method and the average fiber content of the composite was found to be 52% by weight.
[0137] Example 10 - Providing glass fibers with a sizing agent having poly(DL-lactide / glycolide) (PDLG) as a compatibilizer and incorporating the sized fibers within a poly(DL-lactide / glycolide) matrix to form a poly(DL-lactide / glycolide) glass fiber reinforced composite material which is further processed to form a composite plaque.
[0138] Epoxy-functional, silane-treated glass fibers were prepared as described in Example 8 above.
[0139] 30 g of acid functionalized poly(DL lactide / glycolide) 50 / 50 from Corbion with IV of 0.4 and acid value of 4.1 mg KOH / g was dissolved in 1500 g of acetone for 1 hour. After complete dissolution, triethylamine was added in a 1:1.3 molar ratio to the acid to neutralize the acid end groups. After stirring the solution for 15 minutes, the polymer solution was slowly added to ASTM Type II purified water. After 24 hours of evaporation to remove the acetone, an aqueous dispersion of about 3 wt% was obtained. The average particle size (z-average) measured by DLS (Malvern ZetaSizer-nano) was found to be 46 nanometers, with a D90 of 46 nm.
[0140] The silane-treated glass fiber was further treated with the above-mentioned polymer nano-dispersion in an off-line reel-to-reel sizing applicator system by passing the glass fiber through a bath of the above-mentioned polymer nano-dispersion in a continuous manner. The line speed was 5 m / min. The sized fibers were collected on another perforated SS core. The fibers were vacuum dried at room temperature and then cured at 90°C for 16 hours to promote the reaction of the -COOH end groups of the compatibilizer polymer with the epoxy ends of the silane already covalently bonded to the glass surface. The TEA present at the reaction sites acted as a catalyst and was finally removed by applying a vacuum.
[0141] Once cured, the glass samples were tested for the presence of a sizing layer via the TGA loss on ignition method, and the results confirmed the presence of a 1±0.5 wt. % coating on the glass fibers.
[0142] A 10 wt% solution of high molecular weight poly(DL lactide / glycolide) 85 / 15 with an IV of 2.3 dL / g was prepared in acetone at 50°C. A bundle (576 filaments) of sized fibers (having an average diameter of 16 microns) of the above PDLG was coated with PDLG 85 / 15 by passing it through a polymer solution bath with a continuous reel-to-reel applicator system. The polymer solution bath was equipped with rollers and pins to spread the fibers for better wetting. The solvent was removed by passing the coated fibers through an anti-solvent (alcohol) bath at room temperature. The line speed was 2 m / min. The coated fibers were air-dried for 24 hours. After drying, the coated fibers appeared as a thin and narrow tape. The coated and dried fibers were analyzed for fiber / polymer content via a LECO TGA701 heat loss method. The polymer content was 32.6 wt%.
[0143] The resulting composite tapes were cut into long strips of 100 mm length, and a certain amount was stacked in a uniform direction and spread into the cavity of a preheated mold to prepare samples for mechanical testing. On the coated fiber stack, an additional polymer (Purasorb PLDG85 / 15) film was added as a top layer to make 50 wt% fiber in the final molded part. The mold cavity was 100 mm x 100 mm x 1 mm. These coated fiber bundles and polymer film layers were then heated above the softening temperature of the polymer, pressed, and subsequently cooled and removed from the mold. Composite plaques were obtained and used for analytical purposes.
[0144] The composite plaques were cut into rectangular coupons (target 50x13x1 mm; LxWxT) and subjected to flexural property testing (3-point-bending test) according to ASTM D7264 / D7264M-15 using a Lloyd universal mechanical tester equipped with a 3 point bend fixture and a 2.5 kN load cell. A span to thickness ratio of 16:1 was used. With a standard width of 13 mm, the length of the specimen was approximately 20% longer than the support span (10% on each side). The average strength of the six samples tested was measured to be 770.7±131 MPa (770% improvement from the base polymer's strength of 100 MPa) and the modulus of elasticity was measured to be 23.9±5.4 GPa (570% improvement from the base polymer's strength of 4.2 GPa). The samples tested were analyzed for fiber content via TGA heat loss method and the average fiber content of the composite was found to be 55.7 wt%.
Claims
1. 1. A resorbable, biocompatible glass fiber coated with a sizing agent, the sizing agent comprising a thermoplastic, resorbable, biocompatible compatibilizer covalently bonded to the glass fiber through a coupling agent having at least one silane moiety, the glass fiber having an apparent interfacial shear strength with a reference matrix polymer determined in a single fiber pull-out test, the apparent interfacial shear strength being at least 10% higher than the apparent interfacial shear strength of a bare glass fiber with the same reference matrix polymer.
2. 10. The coated glass fiber of claim 1, wherein the coated glass fiber contains an amount of volatile tertiary amines of less than 10 ppm, or from 0.1 ppm to 10 ppm.
3. 3. The coated glass fiber of claim 1 or 2, wherein the sizing agent is surfactant-free, preferably the coated glass fiber is surfactant-free.
4. 4. The coated glass fibre according to claim 1 , wherein the coated glass fibre has an apparent interfacial shear strength with a reference matrix polymer determined in the single fibre pull-out test, which is at least 20%, in particular at least 30%, higher than the apparent interfacial shear strength of a bare glass fibre with the same reference matrix.
5. 5. The coated glass fibre according to any one of claims 1 to 4, wherein the coated glass fibre has an apparent interfacial shear strength with a reference matrix polymer determined in the single fibre pull-out test, the apparent interfacial shear strength being at least 10 MPa, in particular at least 15 MPa, more in particular at least 20 MPa, more in particular at least 30 MPa, preferably at least 40 MPa, even more preferably at least 50 MPa.
6. A method for producing resorbable and biocompatible glass fibres coated with a sizing agent, in particular coated resorbable and biocompatible glass fibres according to any one of claims 1 to 5, comprising the steps of: a) glass fibers, a coupling agent having at least one epoxy moiety and at least one silanol group in a liquid medium; and a reaction product of the reaction of a compatibilizer with a volatile tertiary amine in a liquid medium, wherein the compatibilizer is a thermoplastic, resorbable and biocompatible polymer containing carboxylic acid end groups; coating the glass fibers with a sizing composition by contacting the glass fibers with a sizing composition; b) subjecting the coated glass fibers to a drying step; c) subjecting the dried coated glass fibers to a curing step at elevated temperature; d) subjecting the cured coated glass fibers to a step of evaporating the volatile tertiary amine. The method comprising the steps of:
7. The method of claim 6 , wherein the tertiary amine acts as a catalyst for the reaction between the epoxy moiety and the neutralized compatibilizer.
8. 8. The method of claim 6 or 7, wherein the coupling agent and the reaction product of the reaction of the compatibilizer with the volatile tertiary amine are present in the same liquid medium.
9. 8. The method of claim 6 or 7, wherein the coupling agent and the reaction product of the reaction of the compatibilizer with the volatile tertiary amine are present in different liquid media, and the glass fiber is first contacted with the coupling agent in a liquid medium and then with the reaction product of the reaction of the compatibilizer with the volatile tertiary amine in a liquid medium, optionally subjected to a drying and / or curing step between contact with the coupling agent and contact with the product of the reaction of the compatibilizer with the volatile tertiary amine.
10. 10. The method according to any one of claims 6 to 9, wherein the product of the reaction of the compatibilizer with the volatile tertiary amine is in an aqueous medium, preferably said product of said reaction of the compatibilizer with the volatile tertiary amine is dispersed in said aqueous medium in the form of a microdispersion, preferably in the form of a nanodispersion.
11. 11. The method of any one of claims 6 to 10, wherein the volatile tertiary amine is selected from the group comprising trimethylamine, triethylamine, tripropylamine, tributylamine, ethyldimethylamine, methyldiethylamine, dimethylethanolamine, diethylethanolamine, N'-methylmorpholine, N'-ethylmorpholine, pyridine, 2-methylpyridine, 3-methylpyridine, 4-methylpyridine and 2,6-lutidine.
12. The method of any one of claims 6 to 11, wherein at least a portion of the tertiary amine is removed under reduced pressure.
13. The compatibilizer is selected from the group consisting of polylactide (PLA), poly-L-lactide (PLLA), poly-DL-lactide (PDLLA), polyglycolide (PGA), poly(ε-caprolactone) (PCL), copolymers of glycolide, glycolide / trimethylene carbonate copolymer (PGA / TMC), lactide / tetramethylglycolide copolymer, lactide / trimethylene carbonate copolymer, lactide / d-valerolactone copolymer, and the like. polymer, lactide / ε-caprolactone copolymer, L-lactide / DL-lactide copolymer (PLDLA), glycolide / L-lactide copolymer (PGA / PLLA), polylactide-co-glycolide, lactide / glycolide / trimethylene carbonate terpolymer, lactide / glycolide / ε-caprolactone terpolymer, PLA / polyethylene oxide copolymer, asymmetric 3,6-substituted poly-1,4-dioxane 13. The method of claim 6 or the glass fibre of claim 1, further comprising a polymer selected from the group comprising: β-hydroxyvalerate copolymer (PHB / PHV), poly-β-hydroxypropionate (PHPA), poly-p-dioxanone (PDO), poly-d-valerolactone-poly-ε-caprolactone, poly(ε-caprolactone-DL-lactide) copolymer, polyesters of oxalic acid, poly-β-malic acid (PMLA), poly-β-alkanoic acids, polyorthoesters, poly(ester anhydrides), and mixtures thereof, in particular a polymer selected from the group comprising polylactide, poly(lactide-co-glycolide), poly(lactide-co-ε-caprolactone), polyglycolide (PGA), and poly(ε-caprolactone) (PCL).
14. A kit of parts suitable for coating resorbable, biocompatible, preferably bioactive, glass fibres, comprising: a compatibilizer comprising an amount of a thermoplastic, resorbable and biocompatible polymer containing a carboxylic acid moiety; tertiary amines, and Coupling agents having at least one epoxy moiety and at least one silane moiety The kit of parts.
15. A composite comprising a plurality of glass fibres according to any one of claims 1 to 5 or the product of the method according to any one of claims 6 to 13 embedded in a resorbable and biocompatible polymer matrix.
16. 16. The composite according to claim 15, wherein the composite is in the form of a unidirectional composite tape or in the form of strands, (cannulated) rods, tubes, pellets or granules, in particular in the form of a unidirectional tape.
17. A medical device comprising a plurality of glass fibres according to any one of claims 1 to 5, or a product of the method according to any one of claims 6 to 13, or a composite according to claim 15 or 16.
Citation Information
Patent Citations
Hybrid fiber materials
CN106149127A
Biocompatible composite materials and their use
JP2012524569A
Functional composite particles and dental curable composition containing the same
JP2018172333A
Dental composition and dental restoration kit
WO2021059645A1